Landscape variability explains spatial pattern of population structure of northern pike (Esox lucius) in a large fluvial system. Issue 19 (3rd September 2014) - Ouellet‐Cauchon, Geneviève; Mingelbier, Marc; Lecomte, Frédéric; Bernatchez, Louis
Abstract A growing number of studies have been investigating the influence of contemporary environmental factors on population genetic structure, but few have addressed the issue of spatial patterns in the variable intensity of factors influencing the extent of population structure, and particularly so in aquatic ecosystems. In this study, we document the landscape genetics of northern pike (Esox lucius), based on the analysis of nearly 3000 individuals from 40 sampling sites using 22 microsatellites along the Lake Ontario – St. Lawrence River system (750 km) that locally presents diverse degrees of interannual water level variation. Genetic structure was globally very weak (FST = 0.0208) but spatially variable with mean level of differentiation in the upstream section of the studied area being threefold higher (FST = 0.0297) than observed in the downstream sector (FST = 0.0100). Beside interannual water level fluctuation, 19 additional variables were considered and a multiple regression on distance matrices model (R2 = 0.6397, P < 0.001) revealed that water masses (b = 0.3617, P < 0.001) and man‐made dams (b = 0.4852, P < 0.005) reduced genetic connectivity. Local level of interannual water level stability was positively associated to the extent of genetic differentiation (b = 0.3499, P < 0.05). As water level variation impacts on yearly quality and localization of spawning habitats, our study illustrates how temporal variation in local habitat availability, caused by interannual water level fluctuations, may locally decrease population genetic structure by forcing fish to move over longer distances to find suitable habitat. This study thus represents one of the rare examples of how environmental fluctuations may influence spatial variation in the extent of population genetic structure within a given species.